(untitled) (Third Sector Social Economic Review, 2022)
Based on the argument that the health-related, economic, political, social, cultural, and psychological effects of COVID-19 have not created equal experiences for all social groups, this study examines in which groups pandemic has brought stigmatization and inequalities and the intersecting dimensions of this stigmatization and inequalities with different parameters in line with the current literature and data. In light of the results obtained in the study, the ambiguity in the pandemic process, concerns, unpredictability, justifications and explanations, and the identification of ‘initiators, spreaders, and those blameworthy’ has caused stigmatization process and resulted in discriminatory and exclusionary discourse and actions. In specific disadvantaged groups, such as certain ethnic and racial groups, the elderly, immigrants, the poor, those employed in particular sectors, the unemployed, those suffering from chronic illnesses, women, and those unable to access and use digital technologies, the dynamics of the pandemic and its restrictions-based practices have worked against them. Additionally, it has broadened and heightened intra-country, inter-country, and regional inequalities owing to the virus’s impact and issues with employment, education, health care, and social protection. Notwithstanding all of its negative effects, the pandemic era has enhanced collective humanitarian efforts, including helping each other, cooperating, and social support actions from individuals to international organizations. It has also shown the potential power of social solidarity in the battle against multidimensional problems and inequalities.